GROWTH OF SAANEN, ALPINE AND TOGGENBURG GOATS IN THE FEDERAL DISTRICT, BRAZIL: GENETIC AND ENVIRONMENTAL FACTORS - McManus, Concepta (2008)
Data from 1215 kids, with 402 Saanen, 396 Alpine, 200 Toggenburg and 217 ½ Alpine goats, was collected on growth of goats in the Federal District, Brazil from 1995 to 2001. For variance analyses were considered as fixed effect farm, breed, sex, kidding type, month and year of kidding and weight of dam as a covariable. Traits as birth weight and growth from birth to weaning and weaning to first insemination were studied. There was a significant effect of breed, sex and type of kidding on birth weight while weaning weight was only influenced by breed. Month and year of kidding were significant in influencing growth rate after birth. Number of days to insemination weight was influenced by both breed and month of kidding while the insemination weight itself was not influenced by any of the factors studied. Insemination weight was lowly correlated with the other traits in the study, as was to be expected. Days to insemination weight was most highly and negatively correlated with growth rate after weaning and weaning weight showing that faster growing animals that were larger at weaning reached insemination weight more quickly. The correlation between weaning weight and growth rate after weaning was low indicating that animals heavier at weaning did not necessarily grow faster after weaning. Key words: Correlation, growth curve, heritability, housed, weight.